Vídeo educativo sobre sexualidade no envelhecimento: um caminho para o diálogo com a equipe de saúde - Fabrício, Fernanda Alencar de Almeida Pereira (2019)
Introduction: sexuality is a dimension related to human health, being a fundamental component of life. Recognized as a basic need, it is associated with quality of life. Its expression does not cease to exist in aging and its understanding becomes essential for the success of a comprehensive attention in this age group. Objectives: identify in literature scientific evidence that influence the approach of sexuality in elderly people, to know the approach of sexuality in the aging, by health professionals of basic attention and to construct educational video on sexuality in aging that can assist sexuality care in elderly people. Method:it is a qualitative studycarried out in three stages were carried out: the first one was related to the integrative review research, through the search for scientific articles in the databases, focusing on health professionals and sexuality in the elderly person or aging, the second was a cross-sectional study, with qualitative approach, carried out at the Basic Health Units in the city of João Pessoa/PB, with a non-probabilistic convenience sample with health professionals, physicians and nurses, through a semi-structured interview using the content analysis technique to analyze the results. The third step involved the construction of an educational video about aging sexuality, directed to elderly people, for transmission by health professionals.Results: in the first step, the evidence indicates that most health professionals have limited knowledge of attitudes, ranging from less permissive to positive, whose approach to the subject is often not carried out proactively. In the second stage, health professionals were interviewed, and doctors and nurses composed the sample equally. The interview originated five main categories, namely types of approach to sexuality; difficulties to approach; importance of approach; professional indicated to address the sexuality and opinion of the elderly about sexuality according to health professionals.The approach to sexuality is occasional, occurring as a priority, during the cytological collection procedure, especially in the nursing group, not being verified in the doctors’ speech. Most doctors do not proactively address the issue, most of which arises from a potential approach initiated by the elderly person during consultations. Most of the professionals revealed difficulties in this conversation, the main ones being discomfort of the elderly person and lack of training, material and qualification on the subject; in the third step, based on the demands made in the previous phases, an educational video was constructed in a graphic animation format addressing sexuality, its importance, the myths and truths about sexuality in aging, with the intention of providing the message that health professionals are open to discuss the issue. Final Considerations: The video provides information and guidelines in a simple way with the purpose of making communication possible with the elderly person, respecting any degree of education. The goal is to reduce the lack of dialogue that favors the acceptance of the asexual stereotype of the elderly person, a condition that increases the limitations of sexuality in aging